Exploring the non-linear association of daily cigarette consumption behavior and food security- An application of CMP GAM regression - Shafeel Umam; Rubaiya Binte Razzak; Munniara Yesmin Munni; Azizur Rahman (PLoS ONE, 2025)
Background Food insecurity and cigarette smoking are significant public health issues that disproportionately affect vulnerable populations. Previous research often overlooks daily smoking patterns, focusing instead on smoking status or cessation. This study seeks to fill that gap, hypothesizing that food insecurity is positively associated with higher daily cigarette consumption. Methods This study investigates the non-linear association between food security status and daily cigarette consumption using data from the 2022 National Health Interview Survey (NHIS). It introduces a novel statistical approach—the COM-Poisson Generalized Additive Model (CMP-GAM)—to capture the non-linear dynamics between these variables, Results The CMP-GAM model was applied to a sample of 819 adults, controlling for key variables like age, body mass index (BMI), and mental health conditions (anxiety and depression severity). The results indicated that while food security status did not significantly affect daily cigarette consumption, the age of smoking initiation was a strong predictor, with earlier smoking onset leading to higher daily cigarette use. Subgroup analyses among participants with cardiovascular disease and diabetes also did not reveal a significant relationship between food insecurity and smoking frequency. Significance The findings suggest that targeted interventions aimed at preventing early smoking initiation may be more effective in reducing smoking prevalence and improving public health outcomes than addressing food security alone. This study highlights the need for further research into the complex interplay between socioeconomic factors and health behaviors like smoking.